Acceptability of patin fish dried noodles substituted with yellow pumpkin flour in toddler wasting - Fitriani, Fitriani; Yuniarti, Yuniarti; Ambarwati, Ria (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
ABSTRAK Latar Belakang: Upaya penanganan masalah gizi kurang pada balita sangat penting dilakukan agar balita tidak masuk ke dalam kondisi gizi buruk dan menimbulkan masalah kesehatan yang lebih serius. Upaya pemilihan pangan lokal yang berprotein tinggi dapat ditambahkan/disubstitusi pada produk mi. Mi kering ikan patin yang disubstitusi tepung labu kuning dengan komposisi tepung labu kuning 7,5% memiliki kualitas kadar air terbaik berdasarkan SNI 8217-2015), sehingga direkomendasikan untuk dimodifikasi dengan berbagai resep dan teknik pengolahan. Pengolahan mi kering dapat diolah menjadi mi goreng, mi rebus atau variasi lainnya. Penyajian mi instan dalam bentuk mi goreng lebih disukai oleh balita usia 24 - 60 bulan.Tujuan: Menguji daya terima mi kering ikan patin yang disubstitusi tepung labu kuning pada balita gizi kurang di wilayah kerja Puskesmas Telogosari Wetan Kota Semarang.Metode: Jenis penelitian yang digunakan adalah pre-experimental design dengan rancangan one- shot case study. Tahapan penelitian terdiri dari: tahap pembuatan produk dan tahap uji daya terima produk, yaitu dengan 3 modifikasi resep yang akan diberikan pada hari ke-1 sampai hari ke-3, yaitu Mi Gosis (Mi Goreng Sosis), Mi Goreng Telur Puyuh (Mi Teluh) dan Mi Gong (Mi Goreng Kampung).Hasil: Tiga resep modifikasi mi kering ikan patin substitusi tepung labu kuning ini memiliki nilai gizi 224,6 kalori- 385,115 kalori, hal ini dapat memenuhi rata-rata 15% kebutuhan sajian makanan balita sebagai selingan. Pada uji daya terima dari 3 resep, sisa tertinggi (>20%) pada hari ke-2 sebanyak 56,7% balita. Daya terima tertinggi balita adalah pada olahan mi kering ikan patin hari ketiga atau mi goreng kampung yaitu sebanyak 22 orang (73,3%).Kesimpulan: Balita dapat menerima mi kering ikan patin dengan daya terima tertinggi adalah pada olahan mi goreng kampung yaitu sebanyak 22 orang (73,3%).KATA KUNCI: daya terima; mi kering ikan patin tepung labu kuning; 3 modifikasi resep; balita wastingABSTRACTBackground: Efforts to deal with malnutrition problems in toddlers are very important so that toddlers do not enter into malnutrition conditions and cause more serious health problems. Efforts to select high-protein local foods can be added/substituted to noodle products. Dried patin fish noodles substituted with yellow pumpkin flour with a composition of pumpkin flour of 7.5% have the best moisture content quality based on SNI 8217-2015), so it is recommended to be modified with various recipes and processing techniques. Dry noodle processing can be processed into fried noodles, boiled noodles, or other variations. The presentation of instant noodles in the form of fried noodles is preferred by toddlers aged 24 – 60 months.Objectives: This study aimed to test the acceptability of patin fish dried noodles substituted with yellow pumpkin flour  in malnourished toddlers in the working area of the Telogosari Wetan Health Center in Semarang City.Methods: The type of research used is a pre-experimental design with a one-shot case study design. The stages of the research consist of the product Preparation Stage and Product Acceptability Test Stage, namely with 3 recipe modifications that are said to be given on days k-e 1 to 3, namely Mi Gosis (Sausage Fried Noodles), Quail Egg Fried Noodles (Teluh Noodles), and Gong Noodles (Village Fried Noodles).Results: These three modified dry catfish noodle recipes have a nutritional value of 224.6 - 385,115 calories, this can fulfill an average of 15% of toddlers' food needs as a distraction. In the acceptability test of 3 recipes, the highest remaining (>20%) was on the 2nd day for 56.7% of toddlers. The highest acceptability for toddlers is processed dried catfish noodles on the third day or village fried noodles, namely 22 people (73.3%).Conclusions: Toddlers can accept dried catfish noodles with the highest acceptability being KEYWORD: acceptability; dried patin fish noodles yellow pumpkin flour; 3 recipe modifications; toddler wasting Received: 18 Dec 2024; Revised: 26 Apr 2024; Accepted: 24 Jan 2025; Available online: 30 Mar 2025; Published: 30 Mar 2025